2013
DOI: 10.1103/physrevlett.110.170403
|View full text |Cite
|
Sign up to set email alerts
|

Universal Properties of the Higgs Resonance in (2+1)-Dimensional U(1) Critical Systems

Abstract: We present spectral functions for the magnitude squared of the order parameter in the scaling limit of the two-dimensional superfluid to Mott insulator quantum phase transition at constant density, which has emergent particle-hole symmetry and Lorentz invariance. The universal functions for the superfluid, Mott insulator, and normal liquid phases reveal a low-frequency resonance which is relatively sharp and is followed by a damped oscillation (in the first two phases only) before saturating to the quantum cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 26 publications
12
62
4
Order By: Relevance
“…In the disordered phase, we have found that the scalar spectral function has a threshold at ω = 2∆ and no Higgs-like peak. This outcome is in disagreement with a previous QMC analysis which found a peak close to the threshold, which was interpreted as a precursor to the Higgs mode in the disordered phase 23 . A weak peak in the spectral function was also found in a separate QMC analysis 25 , as well as in a NPRG calculation 26 .…”
Section: Summary and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the disordered phase, we have found that the scalar spectral function has a threshold at ω = 2∆ and no Higgs-like peak. This outcome is in disagreement with a previous QMC analysis which found a peak close to the threshold, which was interpreted as a precursor to the Higgs mode in the disordered phase 23 . A weak peak in the spectral function was also found in a separate QMC analysis 25 , as well as in a NPRG calculation 26 .…”
Section: Summary and Discussioncontrasting
confidence: 99%
“…For ε 1, we find indirect evidence for a peak in the spectral function at ω of order T , which may agree with Ref. 23 , although for ε = 1 no such peak is seen. Instead, only a threshold-like behavior is observed at low frequencies.…”
Section: Summary and Discussionsupporting
confidence: 92%
“…Precisely this type of response is measured in the lattice shaking experiment near the superfluid to Mott insulator transition performed by Endres etal 6 . As a result, a sharp peak due to a Higgs excitation appears even in 2D, as supported by a detailed theoretical analysis of this problem, both numerically 5,19,20 and analytically 21 . In particular, the Higgs mode remains well defined even near the quantum critical point because both its energy and width vanish with the same power in the distance from the critical point 5,[19][20][21][22] .…”
Section: Introductionmentioning
confidence: 74%
“…Specifically, at the low dimensions, such fluctuations enhance the decay channel of a Higgs mode into two NG modes so strongly that the Higgs mode is not necessarily well defined [29,[32][33][34][35][36][37][38][39][40]. Hence, in the following, we only consider the case of d = 3, where the Higgs mode is known to be long-lived [29,41,42] so that the use of the two methods is well justified.…”
Section: Methodsmentioning
confidence: 99%